RELIABLE INFORMATION RESILIENCE AT LPP RRI AS A FORM OF DEFENSE OF THE INDONESIAN NATION AND STATE - Sonni Agung Saputra; Totok Imam Santoso; Bastari Raja Tihang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Information resilience is an integral part of non-military defense strategy amidst digital disruption and massive distribution.hoax. Study Thisaims to analyze the role of the Public Broadcasting Institution of Radio Republik Indonesia (LPP RRI) in realizing information resilience as a form of national defense. With a qualitative approach and data collection techniques through interviews, observations, and literature studies, this research This found that RRI plays a strategic function in disseminating reliable information. throughout Indonesia. Findings shows that the existence of RRI's extensive network, editorial neutrality, and the use of multiplatforms are strengths in countering disinformation and strengthening public trust. Research This recommend strengthening human resource capacity, supporting regulations, and expanding strategic cooperation between agencies.